Modification of as Synthesized SBA-15 with Pt nanoparticles: Nanoconfinement Effects Give a Boost for Hydrogen Storage at Room Temperature - Yu Yin (Nature Portfolio, 2017)
Abstract In this work, Pt nanoparticles were incorporated into SBA-15 to prepare the materials for hydrogen spillover adsorption. We provide a direct modification (DM) strategy to improve the content of Pt nanoparticles inside the channels of SBA-15. In this strategy, the Pt precursor was directly incorporated into as synthesized SBA-15 by a solid-state grinding method. The subsequent calcination in air, then H2/Ar gases was conducted to obtain the resultant materials of PtAS. For the samples of PtAS, Pt nanoparticles up to 5.0 wt% have a high dispersion inside the channels of SBA-15. The size of nanoparticles is in control of 3.7 nm. Although much work so far has focused on modification of SBA-15 with Pt nanoparticles. Here, it is the first time the loading amount of Pt nanoparticles raises up to 5.0 wt%, and the location of the Pt nanoparticles is interior channels of SBA-15. We reveal that the high dispersion behaviors of Pt nanoparticles are ascribed to the nanoconfinement effects provided by as synthesized SBA-15. However, the samples derived from template free SBA-15 (PtCS) show sparsely dispersion of Pt nanoparticles with the size of 7.7 nm. We demonstrate that the PtAS samples show better hydrogen adsorption performance than PtCS.